Botulinum Neurotoxin for the Treatment of Neuropathic Pain - Egeo, Gabriella; Fofi, Luisa; Barbanti, Piero (Frontiers in Neurology, 2020)
Botulinum neurotoxin is widely used for central and peripherical neurological conditions. Initially used to treat muscle spasticity, over the years its use has been expanded also to other neurological disorders. This review summarizes the evidence from the published literature regarding its effect on neuropathic pain. Almost all investigations were performed using onabotulinum toxin type A (BoNT/A). Most studies provided positive results, even though toxin formulation, dose, dilution, injection techniques and sites are heterogeneous across studies. Future larger, high quality, specifically designed clinical trials are warranted to confirm botulinum neurotoxin efficacy in neuropathic pain.